Audit of In-Hospital Mortality from a Medical Oncology and Hemato-Oncology Center with the Emphasis on Best Supportive Care - Sundriyal, Deepak; Nath, Uttam Kumar; Kumar, Parmod; Gupta, Sweety; Joseph, Deepa; Vaniyath, Sudeep; Chetia, Rituparna; Bakliwal, Anamika; Chattopadhyay, Debranjini; Dhingra, Gaurav; Sehrawat, Amit (South Asian Journal of Cancer, 2022)
Background and Objectives The newly established medical oncology and hemato-oncology center at the All India Institute of Medical Sciences (AIIMS), Rishikesh, Uttarakhand, India, provided us an opportunity to audit in-hospital mortalities with a vision that the audit will serve as a standard for ceaseless improvement. Aim of the study was to initiate a vigorous process for the evaluation of all-cause mortality in patients suffering from cancer.Methods An audit of all in-hospital deaths that occurred during the year 2019 was performed, and comprehensive scrutiny of various parameters (demographic, clinico-pathological, therapeutic, causes of death) was done. Reviews from two independent observers sharpened the infallibility of the audit. The lacunae in the existing practices and the scope for further improvement were noted.Results Forty-five in-hospital deaths were registered during the study period (January–December 2019). The majority of the deaths occurred in patients with advanced stage of malignancy ([n = 31] 68.8%). Most common causes of death were progressive disease, neutropenic, and non-neutropenic sepsis. Chemotherapeutic agents, growth factors, blood components, and antibiotics were found to be used judiciously as per institutional policy. The reviewers emphasized on the use of comorbidity indexes in the treatment planning and avoiding intensive care unit referrals for patients receiving best supportive care (BSC). Emphasis was put on providing only BSC to the patients with a very limited life expectancy. Emphasis was also laid down on record of out of the hospital deaths.Interpretation and Conclusion The audit disclosed areas of care which require further improvement. The mortality audit exercise should become a regular part of evaluation and training for the ongoing and future quality commitment. This should impact the clinical decision making in an oncology center providing quality care to the terminally ill patients.
Keywords: best supportive care; in-hospital deaths; mortality audit; neutropenic sepsis; non-neutropenic sepsis; progressive disease